Demystify the blackbox model of automated detection of lung and kidney diseases from X-ray and CT radiographs - Islam, Md. Nazmul (Brac University, 2023)
This project report is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science and Engineering, 2021.